Deteksi Hewan Secara Real-Time Menggunakan Algoritma You Only Look Once (YOLO) - Fersellia Fersellia; Anisa Lutfiyani; Fahmi Fachri; Endang Wahyuningsih (Yayasan Literasi Sains Indonesia, 2026)
Forest areas in Indonesia are very vital and are the lungs of the world. The government and forest police need assistance in tackling forest fires and animal rescue, especially system assistance that can be used in real-time so that rescue and first aid can be carried out immediately. This is what moves the research team to conduct research in making a prototype of a real-time animal detection system. The goal to be achieved is to help forest police, SAR teams and teams from local governments to detect animals in forest areas in real-time. This research is quantitative research using experimental methods. The subject of our research is the image images that we get in real time from the webcam, especially animal images. Data was collected using the help of a webcam installed in the forest area. Image and video processing is done using the You Look Only Once (YOLO) and Convolutional Neural Network (CNN) algorithms. This study obtained 82% accuracy, 86.11% precision and 82% recall. The camera angle shooting from the front gets 100% accuracy.